BOOK REVIEW OF THE NOVEL SAFE HAVEN BY NICHOLAS SPARKS - Permana, Bogi Hanni (LANTERN (Journal on English Language, Culture and Literature), 2015)
Novel Safe Haven that is chosen by the writer is a novel that has theme of love. Based on the intrinsic elements of novel, character is one of the important elements in a novel. Because of the character, the story could run and seem more alive. Therefore, the writer of this paper focuses on the life of the main character in the novel Safe Haven. Based on the description above, the writer determines a title Book Review of the Novel Safe Haven by Nicholas Sparks as his final project report